Integrasi Program Nutrisi Gratis dalam Pendidikan sebagai Komponen Manajemen Pendidikan Nasional: Penelitian - Nabilah Khonsa; Hamidatul Khalifah; Siti Zulaikha; Muh.Takdir (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Optimal nutrition plays a vital role in supporting student attendance, cognition, and academic achievement. However, in many countries, including Indonesia, the integration of nutrition programs into education management remains suboptimal. This article reviews scientific literature on the integration of nutrition into formal education using a Systematic Literature Review (SLR) approach, analyzing sources from 2020 to 2025. Findings reveal a growing research trend focusing on student attendance, learning concentration, and school management effectiveness. Case studies from countries such as Brazil, Japan, and Kenya highlight best practices in cross-sector integration, despite challenges like limited funding, weak inter-ministerial coordination, and low school-level management capacity. The study underscores the need for education policies that embed nutrition as part of school resource management. Recommendations include evidence-based policies, dedicated budgets, capacity building for principals and teachers, and robust monitoring systems. Nutrition programs should thus be viewed not only as health interventions but also as strategic tools to enhance educational quality and equity.